Superspace approach to the renormalization of the O'Raifeartaigh model up to the second order in the linear delta expansion parameter - Abdalla, M. C. B. [UNESP]; Helayel-Neto, J. A.; Nedel, Daniel L.; Senise, Carlos R. (Amer Physical Soc, 2012)
We adopt a superspace/supergraph formalism to pursue the investigation of the structure of one- and two-loop divergences in the frame of the minimal O'Raifeartaigh model that realizes the F-term spontaneous supersymmetry breaking. The linear delta expansion (LDE) procedure is introduced and renormalization is carried out up to the second order in the LDE expansion parameter. In agreement with the nonrenormalization theorem for the (chiral/antichiral) matter potential of N = 1, D = 4 supersymmetry, our explicit supergraph calculations confirm that only the Kahler potential is actually renormalized.